2012
DOI: 10.1177/0091270011412968
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole Impairs the Absorption of Mycophenolate Mofetil But Not of Enteric‐Coated Mycophenolate Sodium in Healthy Volunteers

Abstract: In 2 crossover studies, 12 healthy volunteers (6 male/6 female) received a single oral dose of mycophenolate mofetil (MMF) 1000 mg or an equimolar dose of enteric-coated mycophenolate sodium (EC-MPS) 720 mg fasting with and without coadministered omeprazole 20 mg bid. The plasma concentrations of mycophenolic acid (MPA) and of the inactive metabolite mycophenolic acid glucuronide (MPA-G) were measured by high-performance liquid chromatography (HPLC). In addition, dissolution of MMF 500 mg or EC-MPS 360 mg tabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 33 publications
(81 reference statements)
3
35
1
Order By: Relevance
“…Kees et al demonstrated in vitro that MMF tablets dissolved completely at pH G4.0, but only 47% and 13% of the tablet were dissolved at pH 5 and 7, respectively, after 4 days of omeprazole 20 mg twice daily (27). Although all PPIs have been shown to increase the gastric pH levels to above 4.0, the exact pH achieved and time maintained at pH 94.0 vary widely by patient, PPI used, PPI dose, and PPI frequency (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kees et al demonstrated in vitro that MMF tablets dissolved completely at pH G4.0, but only 47% and 13% of the tablet were dissolved at pH 5 and 7, respectively, after 4 days of omeprazole 20 mg twice daily (27). Although all PPIs have been shown to increase the gastric pH levels to above 4.0, the exact pH achieved and time maintained at pH 94.0 vary widely by patient, PPI used, PPI dose, and PPI frequency (28).…”
Section: Discussionmentioning
confidence: 99%
“…Although data to support conversion from MMF to EC-MPS for gastrointestinal adverse events are limited to open-label, crossover studies, pharmacokinetic studies have shown that MPA exposure in patients given EC-MPS is not adversely effected by PPI (19,25,27). Because a generic is not available, EC-MPS remains a more expensive but potential alternative to MMF in patients requiring a PPI who are at high risk for rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Following administration of MMF, higher ph-levels reduce peak concentrations (C max ) and the AUCs in healthy volunteers diminished significantly. 79 In contrast, C max and AUC were not impacted by the acid-resistant ECMPS formulation. 80 …”
Section: Introductionmentioning
confidence: 95%
“…Omeprazole impairs the absorption of MMF, but not enteric-coated mycophenolate sodium (a formulation therapeutically equivalent to MMF), in healthy volunteers, indicating that impaired absorption of MMF with concomitant PPI is a result of incomplete dissolution of MMF in the stomach at elevated pH 53. Therefore, enteric-coated mycophenolate sodium may be an alternative to immunosuppressant treatment.…”
Section: Circumstance 1: Omeprazole Is Comedicated As a Precipitant Drugmentioning
confidence: 99%